Facial and ocular thermal mapping in black-and-gold howler monkey (Alouatta caraya) by infrared thermography: An ex situ study - da Costa, André Luiz Mota [UNESP]; Silva, Maraya Lincoln; Caiaffa, Mayara Grego; Matos, Flora Nogueira; Gonzaga, Cássia Regina Ramos; de Fátima Sallum Leandro, Shamira; de Medeiros, Marina Alvarado; Teixeira, Rodrigo Hidalgo Friciello [UNESP]; Teixeira, Carlos Roberto [UNESP] (Wiley, 2024)
Background: This study used infrared thermography (IRT) for mapping the facial and ocular temperatures of howler monkeys, to determine parameters for the diagnosis of febrile processes. There are no published IRT study in this species. Methods: Were evaluated images of a group of monkeys kept under human care at Sorocaba Zoo (São Paulo, Brazil). The images were recorded during 1 year, in all seasons. Face and eye temperatures were evaluated. Results: There are statistically significant differences in face and eye temperatures. Mean values and standard deviations for facial and ocular temperature were respectively: 33.0°C (2.1) and 36.5°C (1.9) in the summer; 31.5°C (4.5) and 35.3°C (3.6) in the autumn; 30.0°C (4.3) and 35.6°C (3.9) in the winter; 30.8°C (2.9) and 35.5°C (2.1) in the spring. Conclusions: The IRT was effective to establish a parameter for facial and ocular temperatures of black-and-gold howler monkeys kept under human care.
Keywords: eye; face; infrared; primate; thermography